DIORAMA SEBAGAI MEDIA INTERAKTIF DALAM PEMBELAJARAN SIKLUS AIR DI SEKOLAH DASAR - Sri Haryanti; Fitri Lastini; Ahsanul Huda Susanto; Yenny Widyawati; Anatri Desstya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this research is to explore the use of dioramas as interactive media in learning the water cycle for class V students at SDN 03 Ngepungsari, Jatipuro, Karanganyar. This research method uses a qualitative approach. The research subjects were 11 class V students. Data was collected through observation, interviews, tests and documentation. Data analysis was carried out using the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions. The research results show that the use of dioramas in learning the water cycle makes it easier for students to understand the concepts of the water cycle. Students look active and fully involved in learning, and can explain the water cycle better after using the diorama. The conclusion of this research is that dioramas can be an innovative and interactive medium for science learning in elementary schools, especially for the topic of the water cycle, and can foster students' understanding of this natural phenomenon.